Effects of FABP5 Expression on Clinicopathological and Survival Characteristics in Digestive System Malignancies: A Systematic Review and Meta‐Analysis - Miaoqing Li; Xiaoxia Wang; Jia Guo; Junchen Qu; Yu Cao; Qingkun Song; Jun Lu (Cancer Medicine)
ABSTRACT Background Digestive system malignancies are a major global health burden, and the role of fatty acid binding protein 5 (FABP5) in these tumors remains controversial. Aims This meta‐analysis aimed to evaluate the correlation between FABP5 expression and clinicopathological features, as well as survival outcomes in digestive system malignancies. Materials and Methods Data from 11 studies (1207 patients) retrieved from PubMed, Embase, Cochrane Library, CNKI, and WanFang were analyzed. Results FABP5 overexpression was associated with poorer overall survival (OS), larger tumor size, advanced UICC stage, and increased risk of vascular invasion and lymph node metastasis. Notably, FABP5 overexpression is particularly associated with poorer OS in the subgroup of digestive tract malignancies and larger tumor sizes in the subgroup of Chinese patients. Discussion Cellular experiments demonstrated that FABP5 overexpression enhances proliferation, migration, and invasion in hepatocellular carcinoma (Huh7) and gastric cancer (HGC‐27) cell lines, while FABP5 knockdown reduces these effects. Mechanistically, FABP5 may drive tumor progression through PPARβ/δ signaling, epithelial‐mesenchymal transition induction, angiogenesis regulation, and potential effects on fatty acid metabolism and hypoxia‐related pathways. Conclusion FABP5 overexpression correlates with adverse clinicopathological features and prognosis in digestive system malignancies, suggesting its potential as a biomarker for these tumors. Further research is warranted.